Boosting proactive motor control via statistical learning with brain stimulation - Giulia Ellena; Federica Contò; Michele Tosi; Lorella Battelli (NeuroImage)
Visual statistical regularities are nested patterns of information extracted to build a predictive internal model that guides attentional and motor decisions. Here, we sought to understand the contributions of the left and right frontoparietal areas in modulating the effect of this expectancy implementation on premotor preparation. Healthy subjects were asked to detect a high-contrast stimulus target presented simultaneously with a distractor, with preceding color cues indicating, trial by trial, the pairing between the response hand and the upcoming stimuli locations. Performance was measured at baseline, and immediately after a one-session training on the task. During the training target locations appeared 75% of the time to the right of the distractor, a regularity unnoticed by participants. The training session was paired with unilateral transcranial random noise stimulation (tRNS) or sham stimulation over the left or right frontoparietal cortex in a counterbalanced design. Results showed a significant response bias in reaction times after training, with faster responses for targets to the right of the distractor. This bias was enhanced by right, but not left, frontoparietal stimulation, highlighting a hemispheric asymmetry in proactive motor control. The implicit nature of learning, as evidenced by subjects’ unawareness of probability distributions, underscores how proactive motor control quickly adapts to statistical regularities. Results suggest a dominant role for the right hemisphere in mediating attentional learning effects, with implications for understanding lateralized functions in adaptation of the motor control.